2000
DOI: 10.2116/analsci.16.235
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Matrix Effects for the Analysis of Zinc in Sodium Chloride Using Direct Sample Insertion-Inductively Coupled Plasma Atomic Emission Spectrometry

Abstract: Direct sample insertion (DSI) is an alternative sample introduction technique for the inductively coupled plasma (ICP).A small quantity of the sample is placed in a sample probe and inserted directly into the plasma for vaporization, atomization, excitation and/or ionization. DSI is applicable to solid, powder, as well as liquid samples with 100% sample introduction efficiency. Since the technique was first introduced by Salin and Horlick in 1979, 1 there has been continuous efforts concerning DSI development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…[15][16][17] Plasma excitation conditions and background emission intensity of the ICP correlate with the position of the sample probe in the ICP. 10,11 The background emission starts to drop when a sample probe is inserted into the plasma. 2,10,11 In Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17] Plasma excitation conditions and background emission intensity of the ICP correlate with the position of the sample probe in the ICP. 10,11 The background emission starts to drop when a sample probe is inserted into the plasma. 2,10,11 In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental set-up was similar to the one described previously. 10 Briefly, a Fassel-type ICP torch with enlarged central channel was used (Glass Workshop, Department of Chemistry, University of Alberta, Canada). The internal diameter of the central channel was enlarged to 9.0 mm to accommodate the sample probe.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Upon sample probe insertion into the plasma, the background emission intensities reduce significantly [4][5][6] and the plasma excitation temperature (T exc ) and electron number density (n e ) reduce by thousands of degrees and orders of magnitude, respectively. 7,8 In a previous study, 8 we showed that the extent of reduction in plasma excitation conditions due to sample probe insertion mainly depended on the outer diameter of the probe, regardless of the form (solid rod, solid rod with undercut, and hollow cup with undercut) and material (graphite or molybdenum) of the probe. The probe effects (represented by reduction in Zn II/Zn I ratio) increased with probe diameter.…”
Section: Introductionmentioning
confidence: 83%
“…In DSI-ICP-AES, analyte appearance time, shape (width and height) of the analyte peak, SBR, and background intensity depend on the position of the sample probe in the ICP discharge. [1][2][3][4][5][6][7][8][9][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Generally, increasing the cup position from a lower position of the ICP (e.g., below the top of the load coil) to a higher position (e.g., above the top of the load coil) gives sharper and more symmetrical analyte emission peaks and, therefore, enhanced SBR. The effects of probe position on plasma excitation conditions, however, are rarely discussed in the literatures.…”
Section: Effect Of Probe Insertion On Plasma Excitation Conditionsmentioning
confidence: 99%